Supply Chain Responsiveness Evaluation Using Forecasting and An Integrated Rough Z-number-based SWARA-TODIM Method - Wang, Chia-Nan; Nguyen, Thuy-Duong; Do, Ngoc-Hien (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
In a dynamic environment characterized by rapid market competition and unanticipated changes, supply chains emphasize the cost-effective implementation of responsive strategies. Moreover, enterprises are experiencing the repercussions of substantial economic transformations precipitated by the COVID-19 pandemic. This research paper aims to identify the critical enablers of responsiveness in Vietnam's jewelry supply chain and rank the supply chain responsiveness (SCR) areas. Evaluating and developing in a challenging economic context is essential to support top management in reallocating resources based on a more empirical foundation. This article presents a novel integrated method combining demand forecasting, the rough Z-number, Stepwise Weight Assessment Ratio Analysis (SWARA), and TODIM (Interactive and Multi-Criteria Decision Making in Portuguese). The approach can decrease the number of pairwise comparisons substantially and demonstrate a substantial benefit in managing ambiguous data and ensuring the dependability of the assessment.